Consolidating Democracy: Political Communication and Public Trust in Early Leadership Post-Election in Indonesia - Syukri, Syukri; Baharuddin, Tawakkal; Hassan, Mohd Sufiean (Nyimak: Journal of Communication, 2025)
This study aims to understand the influence of political communication on public trust in the early post-election leadership period in Indonesia, which is often referred to as the honeymoon period. It also aims to address a gap in existing studies by emphasizing the strategic importance of political communication in this critical stage of governmental transition. This study uses a quantitative approach, and the primary data source is represented by the dataset of the Populix survey on?social media users X and TikTok, as well as additional data collected independently, such as scientific articles, news, and website information. The supplemental material was coded?via NVivo 12 Plus by adopting the method of systematic coding. These findings indicate that transparent, open, and interactive political communication is very important in building public trust in new leaders after the elections in Indonesia. Factors such as transparency, openness of information, and effective use of social media and digital platforms are key to strengthening legitimacy and public support while maintaining political stability in democratic consolidation. Furthermore, the public satisfaction levels in the different sectors in?the first 100 days of leadership also indicate a positive relationship between responsive political communication and support and the new government’s legitimacy. Keywords: Political communication, public trust, early leadership, post-election, honeymoon period  ABSTRAKPenelitian ini bertujuan untuk memahami pengaruh komunikasi politik terhadap kepercayaan publik pada masa awal kepemimpinan pascapemilu di Indonesia, yang sering disebut sebagai honeymoon period. Studi ini juga dimaksudkan untuk mengisi kekosongan literatur yang selama ini kurang menyoroti peran strategis komunikasi politik dalam fase krusial transisi pemerintahan tersebut. Penelitian ini menggunakan metode kuantitatif dengan data utama berupa hasil survei Populix yang mencerminkan persepsi pengguna media sosial X dan TikTok, serta data tambahan yang dikumpulkan secara mandiri berupa artikel ilmiah, berita, dan informasi relevan dari situs web. Data tambahan tersebut dianalisis menggunakan NVivo 12 Plus melalui proses coding secara sistematis. Temuan ini menunjukkan bahwa komunikasi politik yang transparan, terbuka, dan interaktif sangat penting dalam membangun kepercayaan publik terhadap pemimpin baru pasca pemilu di Indonesia. Faktor seperti transparansi, keterbukaan informasi, serta penggunaan media sosial dan platform digital secara efektif menjadi kunci memperkuat legitimasi dan dukungan publik, sekaligus menjaga stabilitas politik dalam proses konsolidasi demokrasi. Selain itu, tingkat kepuasan publik terhadap berbagai sektor pada 100 hari pertama masa kepemimpinan juga mencerminkan korelasi positif antara komunikasi politik yang responsif dengan meningkatnya dukungan dan legitimasi terhadap pemerintahan baru. Kata Kunci: Komunikasi politik, kepercayaan pPublik, kepemimpinan awal, pascapemilu, honeymoon period